Co-producing a transition model of care for eating disorders: lessons learned from a multi-perspective qualitative study with young people, carers and mental health professionals - Maria Livanou; Anya Heneghan; Grace Hill; Alanta McKenzie; Marta Marlais; Francesca Marshall; Zara Smalley; Eleni Xanthopoulou; Nora Kornai; Jessica Wilks; Ailsa McKay; Jun Teh; et al. (Journal of Eating Disorders)
Abstract Background The transition from Child and Adolescent Mental Health Services (CAMHS) to Adult Mental Health Services (AMHS) presents significant challenges for young people with eating disorders and their families. These transitions often occur during critical periods of neurological, social-emotional development, and major life changes, all of which can influence broader psychosocial and treatment outcomes. This study represents the initial phase of a broader co-production project aimed at developing a new intervention model, Transition for Eating Disorder Youth intervention (TEDYi), and explored the lived experiences of young people, carers, and mental health professionals during transitions. Methods Fifteen semi-structured interviews were conducted with young people (n = 6) and carers (n = 9), alongside two focus groups involving 12 mental health professionals. These took place across six NHS sites in England, including two adult and four adolescent specialist eating disorder services. Results The data were analysed with Reflexive Thematic Analysis (RTA) which revealed four key themes: navigating the complexity of transitions, we need carers involved, the shadow of separation, and suggestions for the TEDYi intervention related to coping strategies and self-management. Conclusions These findings have significant clinical implications for transitional care, emphasising the need for a more standardised and supportive approach to the transition from CAMHS to AMHS. The forthcoming intervention model seeks to address these challenges, with this study helping to prioritise key areas identified by TEDYi, which has been endorsed as a preparatory resource for enhancing clinical practice.